Dominance of spotted stemborer Chilo partellus Swinhoe (Lepidoptera: Crambidae) over indigenous stemborer species in Africa's changing climates: ecological and thermal biology perspectives. (13th February 2017) - Mutamiswa, Reyard; Chidawanyika, Frank; Nyamukondiwa, Casper
Abstract: Africa hosts several economically significant lepidopteran cereal stemborer species belonging to the Crambidae, Noctuidae and Pyralidae families. The invasive spotted stemborer ( Chilo partellus Swinhoe), which is native to Asia, is one of the most damaging cereal stemborers in Africa. The impact of C. partellus on indigenous stemborer species remains unclear, although recent work demonstrates its increasing ecological influence and numerical advantage over Sesamia calamistis and Busseola fusca in African landscapes. In the present study, we discuss C. partellus dominance under Africa's changing climates and highlight the ecological and thermal physiological factors that may contribute to its dominance over indigenous stemborer species. Chilo partellus is an efficient colonizer and competitor and may have an advantage under limited resources typical under climate change. Its invasion potential may also probably stem from its short generation time, overwintering physiology, temperature and relative humidity resilience, wide host preferences, and asynchrony with its biocontrol agents. Using laboratory experiments, we show that C. partellus has a high basal temperature tolerance and related plasticity compared with S. calamistis and B. fusca. These results indicate that ecophysiology may determine invasion success and thus may explain the relative invasion advantage of C. partellus in African landscapes. We recommend that future climate change work be directed towards more comprehensive stemborer total ecology research, stemborer thermal biology and implications on the efficacy of biocontrol. Specifically, knowledge of stemborer‐natural enemy evolutionary potential is vital for understanding how climate change and variability may shape host‐natural enemy interactions, with implications for pest forecasts, prediction models and pest management.